Statistical Analysis of Partial Discharge Characteristics in Transformer Oil at the “Point-Plane” Electrode at Alternating Voltage - Korobeynikov S.M.; Bychkov A.L.; Chimitova E.V.; Demin V.A. (Problems of the Regional Energetics, 2017)
In this paper, we consider the problems related to measuring and analyzing the characteristics of partial discharges which are the main instrument for oil-filled high-voltage electrical equipment diagnosing. The experiments on recording of partial discharges in transformer oil have been carried out in the “point-plane” electrode system at alternating current. The instantaneous voltage and the apparent charge have been measured depending on the root-mean-square voltage and the phase angle of partial discharges. This paper aimes at carrying out a statistical analysis of the obtained experimental results, in particular, the construction of a parametric probabilistic model of the dependence of the partial discharge inception voltage distribution on the value of the root-mean-square voltage. It differs from usual discharges which occur in liquid dielectric materials in case of sharp inhomogeneous electrode system. It has been suggested that discharges of a different type are the discharges in gas bubbles that occur when partial discharges in a liquid emerge. This assumption is confirmed by the fact that the number of such discharges increases with increasing the root-mean-square voltage value. It is the main novelty of this paper. This corresponds to the nature of the occurrence of such discharges. After rejecting the observations corresponding to discharges in gas bubbles, a parametric probabilistic model has been constructed. The model obtained makes it possible to determine the probability of partial discharge occurrence in a liquid at a given value of the instantaneous voltage depending on the root-mean-square voltage.